(3MeGjI GdUMajjf hhSGFd GdEYdGe CKfGA GdfRGYGJ GdeSdMI (B:s (3OQGSI JMdjdjI aj VhA CMcGe GdbGfhf GdOhdj GdEfSGfj (B/s - (3MhHg, YHO GdbGOQ HTjQs ((3YeGf (B:s (3OGQ GdKbGaI ddfTQ h GdJhRjY ,s, 2012)
(3MeGjI hSGFd GdGYdGe h GdUMajjfs
(3HHdjhZQGajG (B: (3U(B.279-295s
Keywords: (3GdbGfhf GdOhdj GdbGfhf GdEfSGfjs; (3hSGFd GdEYdGes; (3GdUMGaIs